Investigation of Electronic Conductivity in PbI2:Hf Single Crystals - Furs, T.V.; Hulaj, O.I.; Shemet, V.Ya. (Physics and Chemistry of Solid State, 2019)
A study of the electron-hole conductivity in PbI2 single crystals doped with Hf (0.2 wt %) was conducted using the Wagner polarization cell method. The influence of the Hf alloying admixture (0.2 mass%) on the nature and parameters of lead diiodide’s electronic conductivity has been analyzed. Basing on the received current-potential dependences, p-type conductivity of a single crystal PbI2:Hf was established. The hole conductivity values (sро) were determined in the studied temperature range allowing to construct temperature dependence. The sро value for single crystal PbI2:Hf increased responsively to increasing temperature. For PbI2 and PbI2:Hf, a comparative analysis of the electron-hole conductivity was carried out. This investigation allowed determining the activation energy sро reduction from 0.47 eV to 0.32 eV due to hafnium doping. Consequently, the presence of Hf admixture in PbI2 crystals causes new impurity acceptor levels located at a distance of 0.64 eV from the upper limit of the valence zone.